Monitoring individuals with irregular semiparametric longitudinal behaviour. Issue 1 (2nd January 2018) - Li, Wendong; Dou, Wen; Pu, Xiaolong; Xiang, Dongdong
Abstract : In our daily life, identifying individuals whose longitudinal behaviour differs from the behaviour of those well-functioning individuals is often necessary to avoid some unpleasant consequences. For such purposes, this paper proposes a new charting scheme called semiparametric screening system in cases when the longitudinal behaviour is semiparametric, using SPC and longitudinal data analysis techniques. Various cases, including those with equally spaced data points, unequally spaced data points, temporal correlated data, non-normal data, are discussed by simulations. Also our proposed method is demonstrated using two real data examples about the SHARe Framingham Heart Study of the National Heart, Lung and Blood Institute, and the moisture content of cut tobacco at the outlet collected in Shanghai tobacco group co., LTD of China, respectively. All the numerical results show that the proposed method works well in practice.